Resilient Cities urban nutrition profile: Rwanda - Margolies, Amy; Craig, Hope; Olney, Deanna K. (International Food Policy Research Institute, 2023)
Rwanda is one of the most densely populated countries in Africa. National strategies aim to eliminate chronic malnutrition by 2050. Overall, the country is on track for global nutrition targets for child wasting, overweight and recommended breastfeeding practices. However, there are differences in nutrition challenges between rural and urban areas. The dominance of the agricultural economy at the national level, higher poverty and stunting rates in rural areas has led to a greater focus on promoting food and nutrition security in rural areas.